Single vs two attending senior surgeons: assessment of intra-operative blood loss at different surgical stages of posterior spinal fusion surgery in Lenke 1 and 2 adolescent idiopathic scoliosis - Kwan, Mun Keong; Chiu, Chee Kidd; Chan, Chris Yin Wei (Springer Verlag (Germany), 2017)
Purpose: To assess the pattern of intra-operative blood loss at various surgical stages comparing between single and two surgeons. Methods: Lenke 1 and 2 adolescent idiopathic scoliosis (AIS) patients who underwent instrumented posterior spinal fusion (PSF) surgery from two centres between June 2014 and December 2015 were prospectively recruited into this study. The patients were grouped into Group 1 (single surgeon) and Group 2 (two surgeons). One to one matching using ‘prospective propensity score-matched cohort patient sampling method’ was done. The surgery was divided into six stages: stage 1—exposure, stage 2—screw insertion, stage 3—release, stage 4—correction, stage 5—corticotomies and bone grafting and stage 6—closure. Results: A total of 116 patients were recruited. Of 86 patients who were operated by the two surgeons, 30 patients were matched with 30 patients that were operated by a single surgeon. Operation duration was significantly longer in Group 1 (257.3 ± 51.4 min) compared to Group 2 (164.0 ± 25.7 min). The total blood loss was significantly higher in Group 1 (1254.7 ± 521.5 mL) compared to Group 2 (893.7 ± 518.4 mL). Total blood loss/level fused was significantly higher in Group 1 (117.5 ± 42.8 mL/level) compared to Group 2 (82.6 ± 39.4 mL/level). Group 1 had significantly higher blood loss and blood loss/level fused for stages 1, 2 and 3. Group 2 had lower incidence of allogenic blood transfusion. Conclusions: In PSF surgery for AIS patients, two-surgeon strategy was associated with shorter operation duration, lesser blood loss and lower incidence of allogenic blood transfusion.